Guided graded exercise self-help plus specialist medical care versus specialist medical care alone for chronic fatigue syndrome (GETSET): a pragmatic randomised controlled trial. Issue 10092 (22nd July 2017) - Clark, Lucy V; Pesola, Francesca; Thomas, Janice M; Vergara-Williamson, Mario; Beynon, Michelle; White, Peter D
Summary: Background: Graded exercise therapy is an effective and safe treatment for chronic fatigue syndrome, but it is therapist intensive and availability is limited. We aimed to test the efficacy and safety of graded exercise delivered as guided self-help. Methods: In this pragmatic randomised controlled trial, we recruited adult patients (18 years and older) who met the UK National Institute for Health and Care Excellence criteria for chronic fatigue syndrome from two secondary-care clinics in the UK. Patients were randomly assigned to receive specialist medical care (SMC) alone (control group) or SMC with additional guided graded exercise self-help (GES). Block randomisation (randomly varying block sizes) was done at the level of the individual with a computer-generated sequence and was stratified by centre, depression score, and severity of physical disability. Patients and physiotherapists were necessarily unmasked from intervention assignment; the statistician was masked from intervention assignment. SMC was delivered by specialist doctors but was not standardised; GES consisted of a self-help booklet describing a six-step graded exercise programme that would take roughly 12 weeks to complete, and up to four guidance sessions with a physiotherapist over 8 weeks (maximum 90 min in total). Primary outcomes were fatigue (measured by the Chalder Fatigue Questionnaire) and physical function (assessed by the Short Form-36 physical function subscale); both were self-rated by patients at 12 weeks after randomisation and analysed in all randomised patients with outcome data at follow-up (ie, by modified intention to treat). We recorded adverse events, including serious adverse reactions to trial interventions. We used multiple linear regression analysis to compare SMC with GES, adjusting for baseline and stratification factors. This trial is registered at ISRCTN, number ISRCTN22975026. Findings: Between May 15, 2012, and Dec 24, 2014, we recruited 211 eligible patients, of whom 107 were assigned to the GES group and 104 to the control group. At 12 weeks, compared with the control group, mean fatigue score was 19·1 (SD 7·6) in the GES group and 22·9 (6·9) in the control group (adjusted difference −4·2 points, 95% CI −6·1 to −2·3, p<0·0001; effect size 0·53) and mean physical function score was 55·7 (23·3) in the GES group and 50·8 (25·3) in the control group (adjusted difference 6·3 points, 1·8 to 10·8, p=0·006; 0·20). No serious adverse reactions were recorded and other safety measures did not differ between the groups, after allowing for missing data. Interpretation: GES is a safe intervention that might reduce fatigue and, to a lesser extent, physical disability for patients with chronic fatigue syndrome. These findings need confirmation and extension to other health-care settings. Funding: UK National Institute for Health Research Research for Patient Benefit Programme and the Sue Estermann Fund.